Comparison of range of commercial or primary care led weight reduction programmes with minimal intervention control for weight loss in obesity: Lighten Up randomised controlled trial. (3rd November 2011) - Jolly, Kate; Lewis, Amanda; Beach, Jane; Denley, John; Adab, Peymane; Deeks, Jonathan J; Daley, Amanda; Aveyard, Paul
Abstract : Objective To assess the effectiveness of a range of weight management programmes in terms of weight loss. Design Eight arm randomised controlled trial. Setting Primary care trust in Birmingham, England. Participants 740 obese or overweight men and women with a comorbid disorder identified from general practice records. Interventions Weight loss programmes of 12 weeks' duration: Weight Watchers; Slimming World; Rosemary Conley; group based, dietetics led programme; general practice one to one counselling; pharmacy led one to one counselling; choice of any of the six programmes. The comparator group was provided with 12 vouchers enabling free entrance to a local leisure (fitness) centre. Main outcome measures The primary outcome was weight loss at programme end (12 weeks). Secondary outcomes were weight loss at one year, self reported physical activity, and percentage weight loss at programme end and one year. Results Follow-up data were available for 658 (88.9%) participants at programme end and 522 (70.5%) at one year. All programmes achieved significant weight loss from baseline to programme end (range 1.37 kg (general practice) to 4.43 kg (Weight Watchers)), and all except general practice and pharmacy provision resulted in significant weight loss at one year. At one year, only the Weight Watchers group had significantly greater weight loss than did the comparator group (2.5 (95% confidence interval 0.8 to 4.2) kg greater loss, ). The commercial programmes achieved significantly greater weight loss than did the primary care programmes at programme end (mean difference 2.3 (1.3 to 3.4) kg). The primary care programmes were the most costly to provide. Participants allocated to the choice arm did not have better outcomes than those randomly allocated to a programme. Conclusions Commercially provided weight management services are more effective and cheaper than primary care based services led by specially trained staff, which are ineffective. Trial registration Current Controlled Trials ISRCTN25072883 .